Challenges and Solutions to Global Digital Firms' Exploitation of Small Economies - Tom, Teckshawer (Technium Social Sciences Journal, 2023)
The objective of this study was to assess the exploitation of small economies by global digital firms through tax evasion. It explored the obstacles and suggests how small economies can address these challenges posed by global digital firms that leverage the nature of their service and technology to evade tax. Qualitative research methods were applied with the use of key informant interviews and secondary data collection from relevant literature and reports. Five key informants purposefully selected from Zimbabwe Revenue Authority (ZIMRA) were interviewed. The paper also classifies the nature of services provided by different digital economies. It highlights the challenges being faced by small economies such as the shift in the global business models, tax concept and evasion, international tax regulations, and lack of capacities thereof. The findings indicate how small economies are being taken advantage of by digital giant firms through operating in their jurisdictions, capitalizing on profits, and circumventing tax payments due to non legally binding instruments that compel global firms to comply. Tax evasion by these firms leads to the shrinking of the small economies' tax base. A possible solution to this tax deceitfulness is the adoption of the Organisation for Economic Cooperation and Development(OECD) Pillar One proposal to address and overhaul the current international tax regulations.